Early Urinary Metabolomics in Patent Ductus Arteriosus Anticipates the Fate: Preliminary Data - Bardanzellu, Flaminia; Piras, Cristina; Atzei, Alessandra; Neroni, Paola; Fanos, Vassilios (Frontiers in Pediatrics, 2020)
Introduction. In premature neonates, the persistence of hemodynamically significant ductus arteriosus (hsPDA) can be associated with short- and long-term consequences, impairing their outcome. The correct strategy of management for such condition is under debate, especially regarding contraindications and/or side effects. In the last years, metabolomics was applied to several perinatal, pediatrics or adult conditions to investigate potential biomarkers of disease, resulting useful for the early diagnosis and/or the therapeutic management. Aim of the study. The main purpose of our exploratory study was to asses, through 1H-NMR metabolomics analysis of urinary samples at birth, possible metabolic pathways differentiating, with a significant predictive power, those preterm neonates who will subsequently develop hsPDA and neonates of comparable gestational age (GA) who will undergo spontaneous ductal closure or the persistence or an irrelevant PDA (no-hsPDA). Moreover, we investigated potential prenatal or perinatal clinical factors potentially influencing the development of hsPDA. Matherials and methods: We enrolled n=35 preterm neonates with GA included between 24 and 32 weeks; urinary samples were collected within the first 12 hours of life. Patients were closely monitored regarding intensive care, respiratory support, fluid balance and administered drugs; echocardiogram was performed at 48-72 hours. Results Our results reported a significant correlation between lower GA at birth and the development of hsPDA. Moreover, neonates GA ≤ 30w developing hsPDA were characterized by lower Apgar scores at 1’ and 5’, higher rate of perinatal asphyxia, higher need of delivery room resuscitation and subsequent surfactant administration. Interestingly, metabolomics analysis at birth detected a clear separation between the 1H-NMR urinary spectra of subjects GA ≤ 30w not developing hsPDA (n=19) and those of subjects born at GA ≤ 30w in which hsPDA was confirmed at 48-72 hours of life (n=5). Conclusions This is first study applying metabolomics to investigate PDA condition. Although preliminary and conducted on a limited sample, our results reveal that metabolomics could be a promising tool in the early identification of hsPDA, potentially superior than the clinical or laboratory predictive tools explored to date and even to the clinical observations and correlations in our sample, through the detection of specific urinary metabolites.